Charakterystyka zmienności w kolekcji rodzaju Pisum i Lupinus — wybrane wyniki - Święcicki, Wojciech; Barzyk, Paweł; Kaczmarek, Zygmunt; Kroc, Magdalena; Rybiński, Wojciech; Wilczura, Paulina (Biuletyn Instytutu Hodowli i Aklimatyzacji Roślin, 2018)
-